Celiac disease and non-celiac gluten sensitivity – characteristics and differences - Kulik, Kacper; Fryska, Zuzanna; Wołejko, Adam; Kuciński, Jakub; Semeniuk, Paweł; Matusz, Krystian; Burczyk, Rafał; Górna, Natalie; Łabuda, Adam (Journal of Education, Health and Sport, 2023)
Introduction Celiac disease is a quite common condition resulting from the interaction of genetic, immunological, and environmental factors, with the main environmental factor being exposure to gluten. Non-celiac gluten sensitivity (NCGS) affects individuals without celiac disease or wheat allergy and is characterized by intestinal and extraintestinal symptoms related to the consumption of grain products, without accompanying damage to the intestinal mucosa. Discussion Gluten is a grain protein that is resistant to digestive enzymes and accumulates in the intestines, leading to tissue damage and the release of tissue transglutaminase 2 (tTG2) enzyme, which increases gluten immunogenicity. The presence of HLA-DQ2 or HLA-DQ8 gene variants in the genome is a necessary condition for the development of the disease, but it does not always lead to celiac disease. The pathomechanism of non-celiac gluten sensitivity is not yet fully understood. Diagnosis of celiac disease involves serological tests, genetic tests, and histological examination. Conclusions The only effective treatment for celiac disease is a strict gluten-free diet, which involves eliminating wheat, rye, barley, and triticale from one's diet. Further research is necessary to search for effective therapies. The approach for NCGS involves introducing an appropriate diet - either low FODMAP or gluten-free.